Enhancing the remediation of polyamide microplastics: A comparative study of natural and synthetic coagulants - Ramakrishnan, Devananth; Sathiyamoorthy, Mahenthiran (Frontiers in Environmental Science, 2025)
Polyamide microplastics, which originate from textiles, industrial processes, and everyday consumer products, contaminate waterways, threatening aquatic life, human health, and the environment, emphasizing the urgent need for effective removal technology and sustainable mitigation strategies. This study explores the removal of polyamide microplastics using a coagulation-flocculation- sedimentation (CFS) approach, comparing the effectiveness of natural coagulants (Strychnos potatorum and Cicer arietinum) with the synthetic coagulant alum. The methodology involved optimizing coagulant dosages (50–300 mg/L) and applying a CFS process with rapid mixing (100 rpm, 1 min), slow mixing (30 rpm, 30 min), and sedimentation (30 min). Two sizes of polyamide MPs (<500 μm and >500 μm) were evaluated. The results showed that Strychnos potatorum and Cicer arietinum achieved higher removal efficiencies (up to 92.6% ± 3.21%) for smaller polyamide microplastics (<500 μm) than did alum (up to 87.6% ± 6.5%). Conversely, alum demonstrated superior removal efficiency (up to 91.33% ± 4.16%) for larger polyamide microplastics (>500 μm) compared with Cicer arietinum and Strychnos potatorum (up to 79.6% ± 4.72%). To assess real-world applicability, the method was tested using natural water from Muttukadu Lake. In this more complex matrix, Strychnos potatorum maintained high removal efficiencies, achieving 91.33% ± 3.05% for <500 μm MP and 86.66% ± 3.05% for >500 μm MP, outperforming alum, which showed reduced performance (82.3% ± 9.07% and 78.6% ± 9.50% for small and large MPs, respectively). Cicer arietinum demonstrated moderate efficiency (79.33% ± 4.16% and 76.66% ± 8.6%, respectively), with some sensitivity to natural matrix interference. This study reveals the potential of natural coagulants as viable and sustainable alternatives to synthetic coagulants for the removal of polyamide microplastics, particularly those of smaller sizes. These findings can inform green infrastructure design, enhance environmental sustainability, reduce microplastic pollution, and protect public health, paving the way for innovative, eco-friendly treatment technologies.